Modulation of Mouse Rod Response Decay by Rhodopsin Kinase and Recoverin - Chen, Ching-Kang (Society for Neuroscience, 2012)
Light isomerizes 11-cis-retinal in a retinal rod and produces an active form of rhodopsin (Rh*) that binds to the G-protein transducin and activates the phototransduction cascade. Rh* is turned off by phosphorylation by rhodopsin kinase [G-protein-coupled receptor kinase 1 (GRK1)] and subsequent binding of arrestin. To evaluate the role of GRK1 in rod light response decay, we have generated the transgenic mouse RKS561L in which GRK1, which is normally present at only 2–3% of rhodopsin, is overexpressed by ∼12-fold. Overexpression of GRK1 increases the rate of Rh* phosphorylation and reduces the exponential decay constant of the response (τ(REC)) and the limiting time constant (τ(D)) both by ∼30%; these decreases are highly significant. Similar decreases are produced in Rv(−/−) rods, in which the GRK1-binding protein recoverin has been genetically deleted. These changes in response decay are produced by acceleration of light-activated phosphodiesterase (PDE*) decay rather than Rh* decay, because light-activated PDE* decay remains rate limiting for response decay in both RKS561L and Rv(−/−) rods. A model incorporating an effect of GRK1 on light-activated PDE* decay rate can satisfactorily account for the changes in response amplitude and waveform. Modulation of response decay in background light is nearly eliminated by deletion of recoverin. Our experiments indicate that rhodopsin kinase and recoverin, in addition to their well-known role in regulating the turning off of Rh*, can also modulate the decay of light-activated PDE*, and the effects of these proteins on light-activated PDE* decay may be responsible for the quickening of response recovery in background light.